Gambling Dual Disorder: A Dual Disorder and Clinical Neuroscience Perspective - Szerman, Nestor; Ferre, Francisco; Basurte-Villamor, Ignacio; Vega, Pablo; Mesias, Beatriz; Marín-Navarrete, Rodrigo; Arango, Celso (Frontiers in Psychiatry, 2020)
Several behaviors, including compulsive gambling, have been considered non-substance-related addictive disorders. Categorical mental disorders (e.g., DSM-5) are usually accompanied by very different symptomatic expressions (affective, behavioral, cognitive, substance abuse, personality traits). When these mental disorders occur with addictive disorders, either concomitantly or sequentially over the life span, this clinical condition is called a dual disorder. Gambling disorder (GD) has been associated with other categorical psychiatric diagnoses: attention deficit hyperactivity disorder, depression, bipolar disorder, social anxiety, schizophrenia, substance use disorder, antisocial personality disorder; and dimensional symptoms including higher impulsivity, poorer emotional wellbeing, cognitive distortion, psychosis, deficient self-regulation, suicide, poorer family environment, and greater mental distress. We are calling this clinical condition Gambling Dual Disorder. From a clinical perspective, it is clear that Gambling Dual Disorder is not the exception but rather the expectation, and this holds true not just for GD, but also for other mental disorders including other addictions. Mental disorders are viewed as biological disorders that involve brain circuits that implicate specific domains of cognition, emotion, and behavior. This narrative review presents the state of the art with respect to GD in order to address current matters from a dual disorder, precision psychiatry and clinical neuroscience perspective, rather than the more subjective approach of symptomatology and clinical presentation. This review also presents Gambling Dual Disorder as a brain and neurodevelopmental disorder, including from the perspectives of evolutionary psychiatry, genetics, impulsivity as an endophenotype, the self-medication hypothesis, and sexual biological differences. The wide vision of the disease advances a paradigm shift, highlighting how GD and dual disorders should be conceptualized, diagnosed, and treated. Rethinking GD as part of a dual disorder is crucial for its appropriate conceptualization from the perspective of clinical neuroscience and precision psychiatry.